IMPLEMENTATION OF PRODUCTION SCHEDULE BOARD TO DECIDE STANDARD PRODUCTION TIME IN MANUFACTURING INDUSTRY - Johny Purnomo Joewono; Tan Kui Siong (TEKNOKRIS, 2022)
Manufacturing industry is always a challenging area because of the unpredictable uncertainties and obstacles that might occur anytime throughout the operation. For a company to maintain a profitable growth from time-to-time, different approaches in reducing its operation cost while improving the product quality, operation efficiency, and overall control must be taken to avoid its market share being dominated by the competitors. Those approaches raised the demand of new and evolved management systems and production scheduling system is one of the management tool that been widely used in manufacturing industries and has been proven its capabilities and effectiveness through many success histories. The approach of this project is to implement a production scheduling board on a roof manufacturing company that start seeing the advantages of implementing a production scheduling system on their production floor. The implementation process is comprised of few stages, where each of the stage will be carried out according to the right sequence. The company current production flow was analyzed in order to find out the optimum production time that plays a critical role in deciding the functional ability and reliability of the proposed scheduling board. Throughout the analysis process, modifications on implemented scheduling board were identified so that the system is improved and adopted according to the circumstances. The final output of this project is that the implementation of Production Planning System shows positive and encouraged improvement based on the data collected and compared with data before implementation where significant time were saved by using the scheduling method in managing flow of processes and orders. At the end of this project, an electronic version of scheduling board is constructed based on Microsoft Excel due the problem raised and suggestions given. Recommendations were suggested to improve the overall process of this project.